Analisis Sikap Peduli Lingkungan Siswa Sekolah Dasar di Kota Bandung - Febrialita Salma Dwinandha Putri; Wahyu Sopandi; Atep Sujana; Cut Rania Kirana (Postgraduate, University of Mataram, 2025)
Students' environmental awareness is an important aspect of implementing sustainable education. The environmental awareness of elementary school students is not only important for building awareness of sustainability but also crucial for shaping the character of young generations who care about nature. This research aims to find out how environmental awareness is possessed by students in several elementary schools in Bandung City. Research on the analysis of environmental awareness is needed to ensure that current educational efforts are effective and relevant to the challenges faced by society today. This type of research is descriptive qualitative with data collection techniques by means of observation, interviews and documentation. This research was conducted in four public elementary schools in Bandung City which have similar locations, student criteria and surrounding environmental conditions. Based on the results of the research conducted, it states that, principals and teachers have made efforts to develop various programs that focus on students' environmental care attitudes in Bandung City Public Elementary Schools but are less in accordance with the five indicators of environmental care attitudes, namely environmental awareness, real actions of students, environmental values and ethics, the influence of the social environment, and student discipline due to lack of awareness of students' environmental care attitudes.